Satisfação em relacionamentos amorosos: o papel das estratégias de comportamento, da personalidade e dos valores humanos - Silva Neta, Olindina Fernandes da (2019)
We sought to investigate how dark personality traits, human values, and behavioral strategies in relationships (use of deception, perceived deception, truth-seeking, and enthusiasm) may explain satisfaction in loving relationships. Therefore, three studies were carried out. Study 1 was attended by 223 people and aimed to adapt three scales to the Brazilian context: Enthusiasm and Truth-Seeking in Loving Relationships (ETSLR), Use of Deceit (UD) and Partner Perceived Deceit (PPD). On the ETSLR scale, a Principal Axis Factoring was performed, with an oblique rotation, with two factors. The first factor, Enthusiasm (a = 0.75) was composed of 6 items; the second, Truth-Seeking (a = 0.73), was composed of 5 items. As for the psychometric indicators of the ED and PPD measures, an PCA was also performed, with oblique rotation, which indicated the uniformity of the measures. The first one consists of 9 items (a = 0.82) and the second one composed of 4 items (a = 0.78). Study 2 counted on the participation of 300 people and aimed to confirm the found structures, seeking to verify evidence of factorial validity and internal consistency. Participants responded to the three measures of the previous study. The results indicated a satisfactory adjustment of the measurements, confirming a two-dimensional adjustment of the ETSLR and one-dimensional adjustment of the UD and the PPD. Study 3 aimed to verify the relationship between dark traits, human values, behavioral strategies (use of deception, perceived deception, truth-seeking and enthusiasm) and satisfaction in loving relationships. Participated 300 people, who responded in addition to the measures previously mentioned, the Dark Triad Dirty Dozen, the Factorial Scale of Satisfaction in Relationships of Couples and the Questionnaire of Basic Values. The results showed that these variables were related to satisfaction in love relationships, showing that a positive perception about the partner / relationship increases the levels of satisfaction, while the deception decreases those levels. In addition, he demonstrated how value priorities and dark personality can contribute to the understanding of satisfaction in loving relationships. It is hoped that the objectives were reached and that the present dissertation brings contributions to the understanding of the satisfaction in loving relationships.